2005
DOI: 10.1016/j.expneurol.2004.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Nkx2.2+/Olig2+ oligodendrocyte precursor cells fail to remyelinate the demyelinated adult rat spinal cord in the absence of astrocytes

Abstract: Chronic demyelination is a pathophysiologic component of compressive spinal cord injury (SCI) and a characteristic finding in demyelinating diseases including multiple sclerosis (MS). A better characterization of endogenous cells responsible for successful remyelination is essential for designing therapeutic strategies aimed at restoring functional myelin. The present study examined the spatiotemporal response of endogenous oligodendrocyte precursor cells (OPCs) following ethidium bromide (EB)-induced demyelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
129
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(144 citation statements)
references
References 74 publications
15
129
0
Order By: Relevance
“…On the contrary, in the absence of testosterone or a functional AR, astrocytes remained sparse and P0 + myelin was preferentially detected within the lesion. This observation is consistent with previous studies showing that Schwann cell remyelination occurs in areas of the CNS where astrocytes are absent (9,10).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…On the contrary, in the absence of testosterone or a functional AR, astrocytes remained sparse and P0 + myelin was preferentially detected within the lesion. This observation is consistent with previous studies showing that Schwann cell remyelination occurs in areas of the CNS where astrocytes are absent (9,10).…”
Section: Discussionsupporting
confidence: 83%
“…Thus, within a demyelinated lesion, oligodendrocyte remyelination occurs in regions where astrocytes are present, whereas Schwann cell remyelination preferentially occurs in the absence of astrocytes (7,9,10). Moreover, reducing astrocyte activation by a conditional genetic deletion promoted Schwann cell remyelination (1).…”
mentioning
confidence: 99%
“…This observation is consistent with previous findings that epigenetic signals promoting the differentiation of Nurr1-expressing precursors may emanate from neighboring astrocytes (28). In fact, the role of the astrocyte in directing neurogenesis (15), mediating rescue (14), and potentiating the function of other neural cells is becoming increasingly appreciated (29). In particular, GDNF (one of possibly several natural products of the astrocytic progeny of these hNSCs) shows developmental, trophic, and protective support of DA neurons and promotes effective processing and release of DA (21)(22)(23).…”
Section: Discussionsupporting
confidence: 81%
“…Astrocytes aid remyelination by releasing leukemia inhibitory factor, which stimulates myelination by oligodendrocytes (Ishibashi et al 2006). Whittemore and colleagues showed that in the absence of astrocytes, endogenous OPCs failed to remyelinate the injured spinal cord (Talbott et al 2005). Thus, NSPCs that differentiate into astrocytes may be useful for enhancing recovery after SCI.…”
Section: Generation Of Enhanced Populations Of Differentiated Progenymentioning
confidence: 99%